INVESTIGATING THE IMPACT OF SPASTICITY, DEFORMITIES, AND SENSORY IMPAIRMENTS ON UPPER LIMB FUNCTION IN CEREBRAL PALSY - Dr. Badam Kiran Kumar Reddy (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Cerebral palsy significantly impacts upper limb function due to deformities, spasticity, sensory impairments, and motor control deficits. This study assessed with 150 individuals analyzing motor function, sensory perception, and developmental hand age using standardized tools such as MAULF, FHGT, and WeeFIM. Results revealed that tetraplegic individuals exhibited the most severe functional impairments, while diplegic and triplegic patients demonstrated better outcomes. Sensory deficits were primarily observed in tetraplegics, and hand function peaked around 14 years before declining. Significant correlations between spasticity, deformities, and functional assessments emphasized the need for targeted interventions. The study highlights MAULF and FHGT as essential evaluation tools and recommends refining assessment frameworks to improve treatment monitoring and rehabilitation strategies. Future research should focus on developing standardized, accessible evaluation methods to enhance long-term management and functional outcomes for individuals with cerebral palsy.